A Fault Detection Technique for Series-compensated Lines by TCSC during Power Swing - Saeed Rezaei; Mojtaba Khederzadeh; Majid Gandomkar (Institute of Advanced Engineering and Science, 2018)
The performance of a distance relay is very susceptible to power swing. In order to avoid generating unwanted trip in such condition, a power swing block function (PSB) is used in distance relays. However, if a fault occurs in power swing condition, the relay should distinguish the fault from power swing and generate trip rapidly. Detection a fault in a series-compensated line by Series Capacitor (SC) during the power swing is more complicated than in an uncompensated line due to complex transients generated by series capacitor and the Metal–Oxide Varistor (MOV) operation. In a series-compensated line by TCSC, it is further complicated due to nonlinear variation of compensation level during power swing and fault, moreover, non-unique application mode of TCSC for different faults which is dependent on fault current. This paper examines a method based on negative sequence current to detecting all types of fault during power swing in a series-compensated line by TCSC. The method is tested for different TCSC-compensated power systems include SMIB and 9-bus 3-machine systems. Different types of faults, i.e., symmetrical, asymmetrical and high resistance faults occurring during a power swing are simulated by MATLAB/SIMULINK to examine the algorithm.